Investigation of pollutant reduction by simulation of turbulent non-premixed pulverized coal combustion - Rahmanian, Behnam; Safaei, Mohammad Reza; Kazi, S. N.; Ahmadi, Goodarz; Öztop, Hakan Fehmi; Vafai, Kambiz (Pergamon-Elsevier Science Ltd, 2014)
In this work, a computational model was developed and used to study NOx reduction during pulverized coal combustion. The finite volume method with a structured grid arrangement and a SIMPLE algorithm were utilized to model the pulverized coal combustion process. The effect of dilution of the oxidizer by participating gases including Air, Helium, Argon, Steam and CO2 were studied, and the corresponding reductions in the rate of NO,, production are compared. The cases when 10 and 20 percent of oxidizer was diluted by the participating gases were analyzed. The Probability Density Function (PDF) model was used for modeling the interaction between turbulence and chemistry, and the Discrete Phase Model (DPM) model was used for modeling the solid particle trajectory analysis including the interaction with turbulence. A QUICK scheme was adopted for the discretization of all convective terms of the advective transport equations. The static temperature, mass fraction of pollutant NOx, and velocity distribution along the centerline of the burner as well as temperature and NOx contours for different dilution percentages were presented. It was shown that as result of injection of CO2 into the oxidizer the peak temperature and/or flow velocities of the combustion gases decrease more as compared to injection of steam or other neutral gases. Also, the results showed that the NOx reduction in pulverized coal combustion was highest due to injection of CO2 into the oxidizer in comparison to injection of steam, Argon or Helium. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Turbulent Non-premixed Combustion; Probability Density Function Model; Implicit Solver; NOx Reduction; Discrete Phase Model